2008
DOI: 10.1097/01.pra.0000320120.68928.e5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Treatment for Anxiety in Patients With Dementia: Two Case Studies

Abstract: Anxiety is common in dementia and is associated with decreased independence and increased risk of nursing home placement. However, little is known about the treatment of anxiety in dementia. This article reports results from two patients who were treated with a modified version of cognitive-behavioral therapy for anxiety in dementia (CBT-AD). Modifications were made in the content, structure, and learning strategies of CBT to adapt skills to the cognitive limitations of these patients and include collaterals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…There have to date been no trials of CBT for anxiety symptoms and disorders specifically in the context of dementia, but a report of two case-studies suggest that a modified approach involving caregivers may be effective. 109 Research is also needed into the benefits of combined psychological and pharmacological interventions, compared with either on its own. 110…”
Section: Non-pharmacologicalmentioning
confidence: 99%
“…There have to date been no trials of CBT for anxiety symptoms and disorders specifically in the context of dementia, but a report of two case-studies suggest that a modified approach involving caregivers may be effective. 109 Research is also needed into the benefits of combined psychological and pharmacological interventions, compared with either on its own. 110…”
Section: Non-pharmacologicalmentioning
confidence: 99%
“…The scientific foundation regarding the challenges of caregiving is based largely on caregivers’ self-report [1924] rather than direct or prolonged observation of the caregiving dyad [25, 26]. Unlike the abundance of empirical data (e.g., physical examination findings and results of lab tests and medical procedures) available to clinicians to diagnose health conditions and evaluate response to treatment, objective data are lacking for nuanced assessment of caregiving issues at home.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the programme was the acquisition of knowledge of and skills to adequately cope with MCI-associated symptoms and their consequences. Slight adjustments in the CBT method, like shortening of verbal or written instructions, repeating important information or personal goals and using of reminder cues, requiring the patient to make notes, or simply repeating the ongoing discussion, were made because of the cognitive impairments of the patients [19,37] . The therapists delivering the treatment were all registered psychologists trained and supervised by the first author.…”
Section: Interventionmentioning
confidence: 99%
“…We based our intervention on principles from cognitive-behavioural therapy (CBT) and combined these with psychoeducational and memoryrehabilitation elements. We choose CBT as the psychotherapeutic method, because CBT has been found feasible for MCI patients [17] and has been successfully applied in other cognitively impaired patient groups [18,19] . The pilot study showed the programme to be applicable in this population, yielding promising results, with the programme contributing to the patients' acceptance of their memory impairment and showing a trend for increased marital satisfaction.…”
Section: Introductionmentioning
confidence: 99%